2020
DOI: 10.1002/app.49181
|View full text |Cite
|
Sign up to set email alerts
|

Automotive applications of thermoplastic vulcanizates

Abstract: Thermoplastic vulcanizates (TPVs) are special classes of thermoplastic elastomers, in which dynamic vulcanization of the rubber phase takes place during melt mixing with a semicrystalline thermoplastic matrix phase at elevated temperature. This review article focus on the different types of thermoplastic vulcanizates (TPVs) from various elastomer and thermoplastic blends that are suitable for the automotive applications purpose. A detailed study of the various TPVs based on polypropylene-ethylene propylene die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 78 publications
0
75
0
1
Order By: Relevance
“…Both the statically vulcanized and dynamically vulcanized EOC‐EPDM blend shows the thermal stability up to 400°C. [ 45 ] Therefore, to get a better view of the differences between the thermal stability of statically vulcanized and dynamically vulcanized blend both the graphs are plotted above 300°C in the figure. Following the graph, it can be argued that T i (initial decomposition temperature) and T 50 (temperature at which 50% weight loss takes place) for dynamically vulcanized blend is higher than the statically vulcanized blend.…”
Section: Resultsmentioning
confidence: 99%
“…Both the statically vulcanized and dynamically vulcanized EOC‐EPDM blend shows the thermal stability up to 400°C. [ 45 ] Therefore, to get a better view of the differences between the thermal stability of statically vulcanized and dynamically vulcanized blend both the graphs are plotted above 300°C in the figure. Following the graph, it can be argued that T i (initial decomposition temperature) and T 50 (temperature at which 50% weight loss takes place) for dynamically vulcanized blend is higher than the statically vulcanized blend.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing Figure , correlations were not found between the variation of the filler concentration and the moisture content, although an increase in the moisture content was expected with the increase in the concentration of mineral fillers. [ 16–18 ] In this way, talc had a reduction in moisture content with increasing concentration, contrary to these expectations. Therefore, assuming the value of 500 ppm as the upper limit of the moisture content was observed that the samples Ba_25, Ta_40, and Ba_40 are inside this limit (Ba_40 considering the measurement error).…”
Section: Resultsmentioning
confidence: 69%
“…[ 9–11 ] One of these forms is the blending of thermoplastic elastomers (TPE) to polypropylene, the first having low elastic modulus, high elongation, good impact toughness, and compatibility with polyolefins depending on their chemical structure. [ 12–19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mole percentage of SOFA with respect to BDO in feed and in polymer (determined by 1 H NMR spectroscopy). Note that [CE]/[NDC] ratio is fixed at 1:1.5 2. Glass transition temperatures of soft phase (Tg1) and amorphous part in crystalline hard phase (Tg2).…”
mentioning
confidence: 99%